Business intelligence for improving decision making and organizational performance: A Systematic Literature Review (2019-2024) - Estrella Maldonado, Deyvis; Carlos Diaz, Milagros; Valdiviezo Gonzales, Lorgio (LACCEI, 2025)
The era of digital transformation has led organizations to adopt significant changes due to the growing importance of data. Business intelligence (BI) plays a pivotal role in facilitating data analysis for sound decision making. The present systematic review aims to analyze the current status of the influence of business intelligence on business decision processes. For this purpose, 26 original articles published in the Scopus, ScienceDirect and Scielo databases between January 2019 and June 2024 were examined. Also, a bibliometric analysis was performed using VOSviewer software. The main results showed that business intelligence has generated great benefits for organizations, such as process optimization, increased financial performance and better comprehensive visibility of data. However, major barriers to implementation were also identified, such as the ability to integrate data with other systems and technical skills, as well as high initial costs. It is concluded that the integration of business intelligence tools contributes to making more informed and accurate decisions in organizations, which has an impact on improving their organizational performance and in turn allows them to maintain their competitive advantage.